An Anterior Cruciate Ligament (ACL) Injury Risk Screening and Reduction Program for High School Female Athletes: A Pilot Study - Allison Kuntz; Olivia Peters; Andrew Bello; Ryan Perkins; Ryan Monti; Leigh Murray (International Journal of Sports Physical Therapy, 2022)
# Background